Intervenção governamental e sustentabilidade: relações entre regulamentação, corrupção e desempenho ambiental no G20 - Reis, Júlia Vieira (2025)
Regulations emerge as a response to market failures, with the aim of balancing economic practices and promoting social objectives. They have the potential to help improve environmental performance, especially in contexts involving corruption and governance issues. This study investigates whether regulation and corruption are related to the environmental performance of G20 countries. Using a quantitative approach, indicators related to governance, corruption and environmental performance were collected from the 19 G20 countries and the 27 countries of the European Union, covering the period from 2012 to 2022. The descriptive results showed a generally positive environmental performance and a moderate level of stringency in environmental regulations among the countries in the sample. Regulatory quality and perception of corruption also show moderate results, indicating moderate variability between countries in terms of governance and corruption. The regression tests indicate that state regulatory action, represented by the regulatory quality index, is positively related to environmental performance, showing that more effective regulations contribute to better environmental results. On the other hand, the perception of corruption is negatively related to both environmental performance and regulatory quality, indicating that high levels of corruption compromise the application and effectiveness of regulatory policies. These findings are more significant in countries with less institutional stability, highlighting the importance of a solid institutional environment for the success of initiatives focused on sustainability issues. The results indicate that strengthening regulations and reducing corruption help to promote sustainable development, reinforcing the need for measures to improve governance and transparency in G20 countries.